CARIS: Supporting Agronomic Research - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
To answer the question 'who did what in agronomic research and where ?', the FAO, in collaboration with its member states, created the Current Agricultural Research Information System (CARIS) in 1973. It operates as a decentralized network of 85...